A randomized trial of energy‐restricted high‐protein versus high‐carbohydrate, low‐fat diet in morbid obesity. (13th April 2013) - Dalle Grave, Riccardo; Calugi, Simona; Gavasso, Ilaria; El Ghoch, Marwan; Marchesini, Giulio
<x xml:space="preserve">Abstract</x> Objective Conflicting evidence exists as to weight loss produced by diets with different carbohydrate/protein ratio. The aim was to compare the long‐term effects of high‐protein vs. high‐carbohydrate diet (HPD, HCD), combined with cognitive behavior therapy (CBT). Design and Methods In a randomized trial, 88 obese participants (mean age, 46.7; mean BMI, 45.6 kg m−2) were enrolled in a 3‐week inpatient and 48‐week outpatient treatment, with continuous CBT during the study period. All subjects consumed a restricted diet (1, 200 kcal day−1 for women, 1, 500 for men; 20% energy from fat, <10% saturated fat). HPD derived 34% energy from proteins, 46% from carbohydrates; HCD 17% from proteins, 64% from carbohydrates. The primary outcome was 1‐year percent weight loss. Secondary outcomes were attrition rates and changes in cardiovascular risk factors and psychological profile. Results Attrition rates were similar between groups (25.6%). In the intention‐to‐treat analysis, weight loss averaged 15.0% in HPD and 13.3% in HCD at 1 year, without any difference throughout the study period. Both diets produced a similar improvement in secondary outcomes. Conclusions The relative carbohydrate and protein content of the diet, when combined with intensive CBT, does not significantly affect attrition rate, weight loss and psychosocial outcome in patients with severe obesity.